2018
DOI: 10.1152/ajpgi.00153.2017
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of hepatic stellate cells, mediated by YAP and TAZ, contributes to liver repair and regeneration after liver ischemia-reperfusion injury

Abstract: Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) are key regulators of cell proliferation and organ size; however, their physiological contribution after liver injury has not been fully understood. In this study, we sought to determine the role of YAP and TAZ during liver recovery after ischemia-reperfusion (I/R). A murine model of partial (70%) I/R was used to induce liver injury and study the reparative and regenerative response. After liver injury, there was marked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 41 publications
2
53
0
Order By: Relevance
“…The commitment of BMSCs toward a specific cell type, either of osteogenic or adipogenic lineage, mostly depends on the change of the cell micro-environment, specifically concerning transcriptional regulators (Ullah et al, 2015). Transcriptional co-activator with PDZ-binding motif (TAZ), a transcriptional modulator, is one of such regulators that have key roles in cell proliferation, differentiation and stem cell self-renewal (Konishi et al, 2018; Tang et al, 2016; Xiao et al, 2018). Although TAZ does not harbor a DNA-binding domain, it could interact with different kinds of transcription factors to activate or repress specific gene expression, which might influence cell functions (Kim et al, 2016; Panciera et al, 2017; Xue et al, 2013; Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The commitment of BMSCs toward a specific cell type, either of osteogenic or adipogenic lineage, mostly depends on the change of the cell micro-environment, specifically concerning transcriptional regulators (Ullah et al, 2015). Transcriptional co-activator with PDZ-binding motif (TAZ), a transcriptional modulator, is one of such regulators that have key roles in cell proliferation, differentiation and stem cell self-renewal (Konishi et al, 2018; Tang et al, 2016; Xiao et al, 2018). Although TAZ does not harbor a DNA-binding domain, it could interact with different kinds of transcription factors to activate or repress specific gene expression, which might influence cell functions (Kim et al, 2016; Panciera et al, 2017; Xue et al, 2013; Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…YAP/TAZ activation is required for the mobilization and proliferation of hepatic stellae cells, the endogenous resident adult stem cell pool within the liver that contributes to regeneration following disease or injury. Konishi et al (2018) observed inactivation of the Hippo signaling pathway and concomitant YAP activation specifically in hepatic stellae cells, upon mobilization and proliferation of these cells in response to ischemia-reperfusion injury of mouse liver. Conversely, treatment of mice with verteporfin, a potent YAP/TAZ inhibitor, drastically reduces hepatic stellae cell proliferation and the regenerative capacity of the liver after ischemia-reperfusion injury.…”
Section: Role Of Yap/taz In Hepatic Differentiation and Liver Regenermentioning
confidence: 85%
“…TAZ, a transcriptional modulator, is one of such regulators that have key roles in cell proliferation, differentiation and function . As reported, TAZ could interact with kinds of transcription factors to activate or repress specific gene expression, which might influence cell functions .…”
Section: Introductionmentioning
confidence: 97%